2020
DOI: 10.1002/jts.22590
|View full text |Cite
|
Sign up to set email alerts
|

Social–Emotional Profiles of PTSD, Complex PTSD, and Borderline Personality Disorder Among Racially and Ethnically Diverse Young Adults: A Latent Class Analysis

Abstract: The debate around the construct validity of complex posttraumatic stress disorder (CPTSD) has begun to examine whether CPTSD diverges from posttraumatic stress disorder (PTSD) when it co‐occurs with the diagnosis of borderline personality disorder (BPD). The present study (a) examined the construct validity of CPTSD through a latent class analysis of a non–treatment‐seeking sample of young trauma‐exposed adults and (b) characterized each class in terms of trauma characteristics, social emotions (e.g., shame, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 54 publications
2
27
0
2
Order By: Relevance
“…Here, most studies find clear commonalities between CPTSD and BPD (Ford, 2019 ; Frost, Hyland, Shevlin, & Murphy, 2020 ; Frost et al, 2020 ; Giourou et al, 2018 ; Hyland, Karatzias, Shevlin, & Cloitre, 2019 ; Jowett, Karatzias, & Albert, 2020 ; Jowett, Karatzias, Shevlin, & Albert, 2020 ; Saraiya et al, 2021 ; van Dijke, Hopman, & Ford, 2018 ), specifically regarding affective dysregulation, which is attributed to transdiagnostic risk factors. Several of these studies have used latent class analyses (Frost et al, 2020 ; Jowett et al, 2020 ; Saraiya et al, 2021 ), but also extended analyses such as structure equation modelling have been used (Frost et al, 2020 ; Hyland et al, 2019 ; van Dijke et al, 2018 ) to address limitations in factor analytical methods for discriminative purposes, as BPD and CPTSD have conceptual similarities (Achterhof et al, 2019 ; Ford, 2020 ; Hyland et al, 2019 ). Despite these identified similarities, CPTSD is distinguishable from BPD in these studies, except for one (Saraiya et al, 2021 ), thus also confirming findings from previous studies (Cloitre et al, 2014 ; Ford & Courtois, 2014 ).…”
Section: Differential Diagnosticsmentioning
confidence: 97%
See 1 more Smart Citation
“…Here, most studies find clear commonalities between CPTSD and BPD (Ford, 2019 ; Frost, Hyland, Shevlin, & Murphy, 2020 ; Frost et al, 2020 ; Giourou et al, 2018 ; Hyland, Karatzias, Shevlin, & Cloitre, 2019 ; Jowett, Karatzias, & Albert, 2020 ; Jowett, Karatzias, Shevlin, & Albert, 2020 ; Saraiya et al, 2021 ; van Dijke, Hopman, & Ford, 2018 ), specifically regarding affective dysregulation, which is attributed to transdiagnostic risk factors. Several of these studies have used latent class analyses (Frost et al, 2020 ; Jowett et al, 2020 ; Saraiya et al, 2021 ), but also extended analyses such as structure equation modelling have been used (Frost et al, 2020 ; Hyland et al, 2019 ; van Dijke et al, 2018 ) to address limitations in factor analytical methods for discriminative purposes, as BPD and CPTSD have conceptual similarities (Achterhof et al, 2019 ; Ford, 2020 ; Hyland et al, 2019 ). Despite these identified similarities, CPTSD is distinguishable from BPD in these studies, except for one (Saraiya et al, 2021 ), thus also confirming findings from previous studies (Cloitre et al, 2014 ; Ford & Courtois, 2014 ).…”
Section: Differential Diagnosticsmentioning
confidence: 97%
“…Several of these studies have used latent class analyses (Frost et al, 2020 ; Jowett et al, 2020 ; Saraiya et al, 2021 ), but also extended analyses such as structure equation modelling have been used (Frost et al, 2020 ; Hyland et al, 2019 ; van Dijke et al, 2018 ) to address limitations in factor analytical methods for discriminative purposes, as BPD and CPTSD have conceptual similarities (Achterhof et al, 2019 ; Ford, 2020 ; Hyland et al, 2019 ). Despite these identified similarities, CPTSD is distinguishable from BPD in these studies, except for one (Saraiya et al, 2021 ), thus also confirming findings from previous studies (Cloitre et al, 2014 ; Ford & Courtois, 2014 ). The differences are seen primarily in the phenomenological expression of the disorders; BPD marked by an unstable self-concept, and CPTSD by a more persistent negative self-concept (Frost et al, 2020 ; Jowett et al, 2020 ).…”
Section: Differential Diagnosticsmentioning
confidence: 99%
“…Another research using latent class analysis approach has demonstrated that CPTSD symptoms are distinguishable from BPD symptoms [ 7 ]. However, other analyses in various samples have also shown some overlap between symptom profiles of CPTSD and BPD [ 8 , 9 ]. Here it is important to note that most of the studies following the official diagnostic guidelines of the ICD-11 CPTSD have used self-report measures to assess the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies further supported the validity of the 6-factor symptom structure of CPTSD and its distinction from PTSD [6]. At the same time, researchers have raised the question whether CPTSD is indicative of a more severe form of psychological distress after trauma rather than a disparate constellation of symptoms (e.g., [11,12]. The article by Andreas Maercker [13] gives a comprehensive overview of the development of the CPTSD diagnosis and highlights the growing attention to this research topic.…”
Section: Introductionmentioning
confidence: 99%
“…One of the remaining research questions is how CPTS D can be differentiated from borderline personality disorder (BPD), both descriptively and empirically. There is considerable symptom overlap, which has been addressed by a growing number of studies (e.g., [11,[14][15][16][17]. BPD is characterized by a marked instability in affect, cognitions, behaviour and interpersonal relationships [5].…”
Section: Introductionmentioning
confidence: 99%